Chemistry of recently isolated naturally occurring quinazolinone alkaloids - Mhaske, Santosh B.; N. P. Argade (Tetrahedron, 2006)
The present review portrays a concise account of the isolation, bioactivity, and synthesis of bioactive quinazolinone-based natural products for the period 1983-2005 and the recent developments in the area of complex quinazolinone natural products with a special emphasis on new synthetic routes and strategies. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: 1983-2005; bioactivity; concise account; isolation; natural quinazolinones; synthesis

Construction of unique SCF3-containing building blocks via allylic alkylation of Morita-Baylis-Hillman adducts - Halder, Priyanka; Pol, Mahesh D.; Ahire, Milind M.; Mhaske, Santosh B. (Organic & Biomolecular Chemistry, 2020)
Lewis base-catalyzed allylic alkylation of Morita-Baylis-Hillman adducts with alpha-SCF3 ketones has been demonstrated. The developed strategy provides efficient access to a series of highly functionalized scaffolds featuring trifluoromethanesufinyl motif on a stereogenic carbon.

Construction of tetrahydrobenzo[f]quinoline scaffolds via polar [4+2]-Cycloaddition reaction with arynes as dienophiles - Pandya, Virat G.; Mhaske, Santosh B. (Tetrahedron Letters, 2022)
A transition-metal-free route has been developed for the direct synthesis of biologically significant tetrahydrobenzo[f]quinoline scaffolds. The reaction features polar [4 + 2] Diels-Alder cycloaddition reaction of arynes with a well-designed diene N-Boc protected vinyl tetrahydropyridine, followed by the isomerisation of the double bond leading to the formation of tetrahydrobenzo[f]quinoline scaffolds in good to moderate yields.
Keywords: Aryne; Diels-Alder; Diene; Tetrahydrobenzo[ f ]quinoline